PENGEMBANGAN RUBRIK PERFORMANCE ASSESSMENT BERBASIS KETERAMPILAN PROSES SAINS (KPS) PADA PRAKTIKUM KELAS XI SMA NEGERI PEKANBARUTAHUN AJARAN 2018/2019: Indonesia - tengku idris; Sarah Riswanti (Universitas Islam Riau (UIR) Press, 2020)
This study aims to develop and find out the feasibility of the Science Process Skills (KPS) based performance assessment rubric on the XI class practice of Pekanbaru State High School Academic Year 2018/2019. Research uses the type of Research & Development development using the ADDIE model which consists of stages of analysis, design, development, implementation and testing. But in this study only reached the stage of development (development). In this study there are two types of validation, namely assessment validation sheet and KPS validation sheet. Based on the criteria determined by the selected school, namely the State High School that applies the 2013 curriculum, school accreditation is at level A. Three selected schools are: SMAN 9 Pekanbaru, SMAN 10 Pekanbaru and SMAN 14 Pekanbaru. Retrieval of data in this study was obtained through validation of experts namely evaluation experts, learning experts and teachers. The data analysis technique uses descriptive analysis. The results of this study are in the form of a PPP-based performance assessment rubric on practices. Based on the results of a joint validation from the evaluation expert, material experts and teacher validation that the performance assessment rubric get a very valid category with a feasibility percentage of 95.83% and the results of joint validation from evaluation experts, material experts and teacher validation that PPP questions get very valid categories with eligibility percentages 98.58%. It can be concluded that the PPP-based performance assessment rubric in class XII Pekanbaru State Senior High School practical activities is very feasible to use in the assessment of practical activities.